2009
DOI: 10.1038/emboj.2009.89
|View full text |Cite
|
Sign up to set email alerts
|

SLP-2 is required for stress-induced mitochondrial hyperfusion

Abstract: Mitochondria are dynamic organelles, the morphology of which results from an equilibrium between two opposing processes, fusion and fission. Mitochondrial fusion relies on dynamin-related GTPases, the mitofusins (MFN1 and 2) in the outer mitochondrial membrane and OPA1 (optic atrophy 1) in the inner mitochondrial membrane. Apart from a role in the maintenance of mitochondrial DNA, little is known about the physiological role of mitochondrial fusion. Here we report that mitochondria hyperfuse and form a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
647
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 674 publications
(709 citation statements)
references
References 54 publications
37
647
3
3
Order By: Relevance
“…We found that high cisplatin concentrations induce SLP‐2 expression, which is in agreement with a previous study that suggested an anti‐apoptotic role of SLP‐2 in cells stressed with cycloheximide and UV irradiation 26. High cisplatin concentrations also increased the p‐MEK1/2 and p‐ERK1/2 levels, and decreased the ratio of Bax/Bcl‐2, cleaved caspase‐9/caspase‐9, cleaved caspase‐3/caspase‐3, and cleaved PARP/PARP in cervical cancer cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that high cisplatin concentrations induce SLP‐2 expression, which is in agreement with a previous study that suggested an anti‐apoptotic role of SLP‐2 in cells stressed with cycloheximide and UV irradiation 26. High cisplatin concentrations also increased the p‐MEK1/2 and p‐ERK1/2 levels, and decreased the ratio of Bax/Bcl‐2, cleaved caspase‐9/caspase‐9, cleaved caspase‐3/caspase‐3, and cleaved PARP/PARP in cervical cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…The protein is required for stress‐induced mitochondrial hyperfusion 26. Upregulation of SLP‐2 increases the mitochondrial membrane phospholipid cardiolipin, thus inducing mitochondrial biogenesis 27.…”
Section: Discussionmentioning
confidence: 99%
“…For electron microscopy, sample preparations and imaging was performed as described previously. 52 Isolation of mitochondria. Crude mitochondrial fractions were prepared by differential centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…In agreement, lower H 2 O 2 doses induced mitochondrial hyperfusion associated to decreased Fis1 expression levels and augmented Mfn1 and Mfn2 . Probably hyperfusion represents a cellular defensive response, because elongated mitochondria display higher efficiency in ATP production that may aid the recovery from the oxidative insult (Mitra et al, 2009;Tondera et al, 2009). In addition, the onset of the mitochondrial permeability transition, process frequently followed by mitochondrial network fragmentation and apoptosis, was subject to redox regulation by oxidation of some components of the mitochondrial permeability transition pore (MPTP), such as critical thiols in the adenine nucleotide translocase and nitration of tyrosines of the voltage-dependent anion channel (for a review see Daiber, 2010).…”
Section: The Feedback Loop Between Ros Production and Mitochondrial Dmentioning
confidence: 99%